MANAJEMEN ASET TANAH DI BAWAH JALAN PADA PEMERINTAH DAERAH KABUPATEN SUMBA BARAT - Regina Lorina Dingu; Aminudin Zuhairi; Laurensius Sayrani (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The purpose of this study is to identify and describe the management of fixed assets, specifically land under roads, in West Sumba Regency. This qualitative research involves key informants, including the Secretary of the PUPR Service, the Head of the Regional Asset Management Division at BKAD, the Head of the Regional Asset Administration Sub-Division, and the Head of the Regional Asset Security Sub-Section. The study utilizes Siregar's (2018) framework, which outlines five stages of asset management: inventory, legal audit, asset appraisal, asset optimization, and asset control supervision. The findings reveal that asset management for land under roads in West Sumba Regency is incomplete due to the lack of comprehensive land ownership documentation. Of the five asset stages, the West Sumba district government is assessing the land under the road's fixed assets. The process of assessing fixed assets for land under the road begins with the determination of the West Sumba Regent's Decree regarding determining the status of district roads. Based on this Decree, the Regional Asset Management Sector checks the land over which the road passes according to the Decree, then calculates the area of the road based on the length of the road in the Decree determining road status.